2010
DOI: 10.4103/0019-5545.74307
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity in outpatients of gynecological oncology clinic in a tertiary care hospital

Abstract: Background:Psychiatric morbidity in gynecological oncology patients is relatively less studied.Aims:This cross-sectional observational study was undertaken to assess the common psychiatric disorders in women who consult the gynecological oncology outpatients’ department.Materials and methods:We assessed a total of 101 outpatients who were recruited by convenience method of sampling. The main outcome measures were PRIME-MD PHQ diagnoses, gynecological and sociodemographic profiles.Results:Psychiatric disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 13 publications
(15 reference statements)
4
17
0
Order By: Relevance
“…10 Depressive disorders and anxiety disorders were diagnosed in 42.5% and 16.8% respectively among gynaecology oncology outpatients in a study. 11 The most common psychiatric disorder in the subjects in this study was depression (54%), finding similar to other studies done in gynaecological setup. Among 131 subjects 71 cases (54%) had definitive depressive symptoms and 21cases (16%) had borderline symptoms and 39(29.7%) were normal.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…10 Depressive disorders and anxiety disorders were diagnosed in 42.5% and 16.8% respectively among gynaecology oncology outpatients in a study. 11 The most common psychiatric disorder in the subjects in this study was depression (54%), finding similar to other studies done in gynaecological setup. Among 131 subjects 71 cases (54%) had definitive depressive symptoms and 21cases (16%) had borderline symptoms and 39(29.7%) were normal.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is similar to the study done in a tertiary care hospital which showed the analysis done to compare socio-demographic variables between women with psychiatric morbidity and women without psychiatric morbidity using chi-square test showed no difference of statistical significance. 11 In a study by Bradley S et al showed greater depression and mood disturbance among unemployed and unmarried cancer survivors. 18 For those women with partners, lengthier relationships appeared to offer protection from both depressive and anxiety symptoms..…”
mentioning
confidence: 97%
“…The prevalence of depression of gynecologic cancer patients has been reported to range from 12 % to 55 %, and major depression has been observed to be much more common in cancer patients than in women with benign disease [19,20]. In our study, the prevalence of depression was 26.4 %.…”
Section: Discussionmentioning
confidence: 41%
“…However, the relationship between malnutrition and psychological factors in gynecologic cancer is not clear. In previous studies, gynecologic cancer patients have been found to have significant levels of psychological disorders, particularly depression and anxiety [19,20]. Therefore, identification of the association between psychological factors and malnutrition could have important implications for treatment of patients with gynecologic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Mendonsa et al, revealed 50% of psychiatric morbidity in cancer group as compared to 42% of benign group while Lau et al, showed prevalence of 31% depressive disorders and anxiety disorders of 16%. 33,34 In present study, 65.95% of psychiatric illness was noted in cases as compared to control group of 21.42%.…”
Section: Discussionmentioning
confidence: 41%